2004
DOI: 10.1038/sj.eye.6701515
|View full text |Cite
|
Sign up to set email alerts
|

Prospective survey of adverse reactions to topical antiglaucoma medications in a hospital population

Abstract: Aim To identify the relative incidence and profile of adverse drug reaction (ADR) to various topical ocular hypotensives in a hospital setting. Methods All the patients presenting in outpatients clinic and accident and emergency with an ADR to topical hypotensive agent from August 2000 to January 2001 were included in the study. Details regarding the type date of commencing the treatment, the date of developing ADR, time to resolution of the ADR were noted. Results Over the period of 6 months, 66 patients pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…This was followed by Timolol, Brimonidine and Prostaglandin analogues. This observation was different from other studies in which ADR related to Dorzolamide was less frequent while Brimonidine (Bhatt et al) 12 and Latanoprost (M Alaei et al) 11 were found to be the most frequent offending medications. Since the ADR could also be related to preservatives (Used in the topical drug preparations), it is difficult to make a definite conclusion regarding this observation.…”
Section: Resultscontrasting
confidence: 55%
“…This was followed by Timolol, Brimonidine and Prostaglandin analogues. This observation was different from other studies in which ADR related to Dorzolamide was less frequent while Brimonidine (Bhatt et al) 12 and Latanoprost (M Alaei et al) 11 were found to be the most frequent offending medications. Since the ADR could also be related to preservatives (Used in the topical drug preparations), it is difficult to make a definite conclusion regarding this observation.…”
Section: Resultscontrasting
confidence: 55%
“…For example, the poorly targeted nature of eye drops leads to extensive systemic exposure, which causes as much as 8-53% of glaucoma patients taking topical anti-glaucoma drugs to experience side effects [8, 9]. In the case of intravitreal administration of steroids, unwanted contact with the lens promotes the formation of cataract in 7 – 14% of patients [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Also, the poorly targeted nature of eye drops leads to extensive systemic exposure, which causes 8% to 53% of glaucoma patients taking topical antiglaucoma drugs to experience side effects. 14, 15 Poor patient compliance and low bioavailability of glaucoma drugs create the need for a better delivery method. 16 In this study, we introduced supraciliary delivery to target drug administration adjacent to the ciliary body to maintain high therapeutic drug levels at the site of pharmacologic action in the targeted tissue.…”
mentioning
confidence: 99%